The 2015 CUA-CUOG Guidelines for the management of castration-resistant prostate cancer (CRPC) - Saad, Fred (Can Urol Assoc J, 2015)
Agents that have shown improvements in survival in mCRPC now include abiraterone, enzalutamide, docetaxel, cabazitaxel and radium-223. Bone supportive agents and palliative radiation continue to play an important role in the overall management of mCRPC. Given the complexity, variety and importance of optimizing the use of these agents, a multidisciplinary team approach is highly recommended.